2006
DOI: 10.1074/jbc.m513728200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct hsp70 Domains Mediate Apoptosis-inducing Factor Release and Nuclear Accumulation

Abstract: Although hsp70 antagonizes apoptosis-inducing factor (AIF)-mediated cell death, the relative importance of preventing its release from mitochondria versus sequestering leaked AIF in the cytosol remains controversial. To dissect these two protective mechanisms, hsp70 deletion mutants lacking either the chaperone function (hsp70-⌬EEVD) or ATPase function (hsp70-⌬ATPase) were selectively overexpressed before exposing cells to a metabolic inhibitor, an insult sufficient to cause mitochondrial AIF release, nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
96
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 82 publications
(69 reference statements)
4
96
0
2
Order By: Relevance
“…1 The induction of Hsp70 production in the brain and retina is associated with cellular resistance to various types of damage. 9,32,33 Gadd34 and Hsp70 mRNA levels returned to basal values 24 hours after ischemia, but a second larger peak was observed for PAI1 mRNA. In accordance with our results, Docagne and colleagues 34 reported greater PAI1 mRNA levels between 24 hours and 3 days after middle cerebral artery occlusion in mice.…”
Section: Discussionmentioning
confidence: 95%
“…1 The induction of Hsp70 production in the brain and retina is associated with cellular resistance to various types of damage. 9,32,33 Gadd34 and Hsp70 mRNA levels returned to basal values 24 hours after ischemia, but a second larger peak was observed for PAI1 mRNA. In accordance with our results, Docagne and colleagues 34 reported greater PAI1 mRNA levels between 24 hours and 3 days after middle cerebral artery occlusion in mice.…”
Section: Discussionmentioning
confidence: 95%
“…While we and others have observed that the Hsp72 substrate-binding domain inhibits apoptosis, others have shown that chaperone activity is required to regulate apoptotic signaling (Gotoh et al 2004;Mosser et al 2000;Ruchalski et al 2006). In each of these examples, Hsp72 was expressed under control of the inducible tetracycline promoter, while those studies that reported protection independent of chaperone activity used constitutive Hsp72 expression systems Sun et al 2006;Volloch et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cells overexpressing HSP72 were protected against the apoptogenic effects of AIF targeted to the extramitochondrial compartment, either by microinjection of the recombinant AIF protein or by transfection with AIF. Moreover, it has been reported that the ATPase domain of HSP72 plays a key role in sequestering AIF in the cytosol, thereby inhibiting AIF nuclear translocation [38]. A potential additional mechanism that may contribute to increase the apoptosis resistance in TFK-1 cells is represented by the constitutive expression of pro-survival HSP27 [21,39,40].…”
Section: Discussionmentioning
confidence: 99%